2021
DOI: 10.1128/msystems.00708-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Quantification of Bovine Digital Dermatitis-Associated Microbiota across Lesion Stages in Feedlot Beef Cattle

Abstract: Previous work, primarily in dairy cattle, has identified various taxa associated with digital dermatitis (DD) lesions. However, there is a significant gap in our knowledge of DD microbiology in beef cattle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 44 publications
2
30
0
1
Order By: Relevance
“…T. medium, T. pedis, and T. phagedenis have consistently been found within TAHD lesions (2, 3) as well as within bovine DD lesions (2,3,15,31,(39)(40)(41)(42)(43)(44)(45)(46)(47). Using species specific primers, one or more of these species were identified on inoculated foot swabs in at least one sampling timepoint (Table 2).…”
Section: Pcrmentioning
confidence: 99%
“…T. medium, T. pedis, and T. phagedenis have consistently been found within TAHD lesions (2, 3) as well as within bovine DD lesions (2,3,15,31,(39)(40)(41)(42)(43)(44)(45)(46)(47). Using species specific primers, one or more of these species were identified on inoculated foot swabs in at least one sampling timepoint (Table 2).…”
Section: Pcrmentioning
confidence: 99%
“…P. levii was detectable in all biopsy samples and warrants further investigation into its association with disease onset. Caddey et al [ 22 ] reported that early-stage DD lesions (M1) were associated with P. levii, which was detectable in 100% of the M1 lesion samples biopsied. Unlike in field studies, where DD lesions and their bacterial composition are studied throughout disease development our study identified DD at the beginning of the disease cycle and the corresponding bacteria could reflect the bacterial species present at disease onset.…”
Section: Discussionmentioning
confidence: 99%
“…Within both these groups there were no DD lesions present and the skin was intact. No biopsies were therefore taken as we know from our previous work the bacterial composition of non-DD biopsies [ 22 ]. Additionally, we did not want to compromise calf welfare any further by inflicting more pain and stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations